Evidence of deep mixing in IRS 7, a cool massive supergiant member of the Galactic nuclear star cluster. Issue 2 (25th August 2022) - Guerço, Rafael; Smith, Verne V; Cunha, Katia; Ekström, Sylvia; Abia, Carlos; Plez, Bertrand; Meynet, Georges; Ramirez, Solange V; Prantzos, Nikos; Sellgren, Kris; Hayes, Cristian R; Majewski, Steven R
ABSTRACT: The centre of the Milky Way contains stellar populations spanning a range in age and metallicity, with a recent star formation burst producing young and massive stars. Chemical abundances in the most luminous stellar member of the nuclear star cluster (NSC), IRS 7, are presented for 19 F, 12 C, 13 C, 14 N, 16 O, 17 O, and Fe from a local thermodynamic equilibrium analysis based on spherical modelling and radiative transfer with a 25-M⊙ model atmosphere, whose chemistry was tailored to the derived photospheric abundances. We find IRS 7 to be depleted heavily in both 12 C (∼–0.8 dex) and 16 O (∼–0.4 dex), while exhibiting an extremely enhanced 14 N abundance (∼+1.1 dex), which are isotopic signatures of the deep mixing of CNO-cycled material to the stellar surface. The 19 F abundance is also heavily depleted by ∼1 dex relative to the baseline fluorine of the NSC, providing evidence that fluorine along with carbon constrain the nature of the deep mixing in this very luminous supergiant. The abundances of the minor isotopes 13 C and 17 O are also derived, with ratios of 12 C/ 13 C ∼ 5.3 and 16 O/ 17 O ∼ 525. The derived abundances for IRS 7, in conjunction with previous abundance results for massive stars in the NSC, are compared with rotating and non-rotating models of massive stars and it is found that the IRS 7 abundances overall follow the behaviour predicted by stellar models. The depleted fluorine abundance in IRS 7 illustrates, for the first time, the potential of using the 19 F abundance as a mixing probe in luminous red giants.